RELEVANSI KURIKULUM SMK DENGAN KEBUTUHAN DUNIA USAHA DAN DUNIA INDUSTRI DI KOTA SORONG PROVINSI PAPUA BARAT - Roberto W. Marpaung, - (2019)
A large number of unemployment of people graduating from vocational schools became the background of this research. The writer also considered the President's Instruction number 9 in 2016 on revitalization of vocational schools as one of the research problem. The results of the research are expected to describe the curriculum quality can be considered for policy making on education especially on vocational education. The main research problem was how the vocational schools affect the development of industry and company in Sorong City The Province of West Papua? There were three specific research problems; 1) how is the description of vocational schools' curriculum in Sorong City The Province of West Papua?; 2) How is the description of industry and company needs in case of employment in Sorong City The Province of Papua Barat?; and 3) is the vocational schools' curriculum relevant to the industry and company needs in Sorong City The Province of West Papua? In general, this research was aimed at describing the impact of vocational schools to the development of industry and company in Sorong City The Province of West Papua. Specifically, this research was aimed at 1) describing vocational schools' curriculum in Sorong City The Province of West Papua, 2) describing the need of industry and company in case of employment in Sorong City The Province of West Papua, and 3) describing whether the vocational schools' curriculum relevant to the industry and company needs in Sorong City The Province of West Papua. The research method used was qualitative research method by using case study approach. The data collection techniques consist of interview, observation and documentation. The result of the research showed that the vocational schools' curriculum was not wholly relevant to the industry and company needs in Sorong City The Province of West Papua. Therefore, the government and all related education practitioners need to reevaluate and supervise the curriculum implementation by vocational schools in Sorong City The Province of West Papua. The vocational schools' curriculum must be relevant to the company and industry needs by linking and matching the curriculum to the company and industry needs.